KEBIJAKAN AMERIKA SERIKAT TERHADAP PENIRUAN TEKNOLOGI ALUTSISTA UDARA OLEH TIONGKOK PADA MASA PEMERINTAHAN PRESIDEN DONALD TRUMP - Nihayati, Arina; Olivia, Yessi (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
This research analyses the United States (US) foreign policy on dealing with cyber threats coming from China. These threats include state-sponsored intellectual theft, cyber espionage and evasion of export control laws. President Barack Obama struck a deal on intellectual aircraft theft with Xi Jinping but the deal was not effectively implemented. Under the administration of Donald Trump, the US rescinds the Obama?s administration strategy and replaces it with the National Security Presidential Memorandum 13 (NSPM-13). This research uses the perspective of neo-realism which focuses on the impact of the anarchic international on states behavior. It applies the rational actor model in the formulation of foreign policies. This research relies on data collected from books, journals, and websites.This study shows that the decision to release Presidential Memorandum 13 was based on the calculation that China threatening America defense and economy. NSPM 13 demonstrates to strengthening America?s cybersecurity capabilities and securing America from cyber threats. This policy was in line with Donald Trump's America First doctrine where it sees the world through the lens of realism of a zero sum relationship. Keywords: America First, China Threat, Air Vehicle, Cyber Threat, Cyber Espionage, US Cyber Policy, NSPM-13